KEMAMPUAN PROFESIONAL GURU TERHADAP PENERAPAN MULTIMEDIA INTERAKTIF DALAM PEMBELAJARAN DI UPT SPF SMPN 21 MAKASSAR - Nurdin; Akram; Fathihatus Sholihah (STKIP Subang, 2024)
The main problem in this study is how the professional ability of teachers towards the application of interactive multimedia in learning at UPT SPF SMPN 21 Makassar. This study aims to determine the professional abilities of teachers towards the application of interactive multimedia in learning at UPT SPF SMPN 21 Makassar. The type of research used in this research is quantitative research with survey method. Data analysis techniques using quantitative descriptive statistical analysis. The sample in this study were all teachers at UPT SPF SMPN 21 Makassar, totaling 49 people. The results showed that around 81.6% to 93.9% of teachers have understood the concepts, structures, and design principles of interactive multimedia well. About 73.5% to 81.6% of teachers are able to understand and identify competency standards and align the use of multimedia with basic competencies. Around 77.5% to 83.6% of teachers feel able to design, produce, and apply innovative methods in developing multimedia for learning. About 71.4% to 87.7% of teachers have engaged in a regular reflection process to improve learning practices with interactive multimedia. And about 51% to 79.6% of teachers have utilized multimedia technology and software for learning. Based on the research results above, it can be concluded that the professional ability of teachers towards the application of interactive multimedia in learning at UPT SFP SMP Negeri 21 Makassar is quite good.